The Effect of Consumer Price Index And The Amount Of Money Circulation On Net Assets Value Of Sharia Mutual Funds - Yayang Kirana Dewi; Fanji Farman; Lisna Lisnawati (Journal of Business, Accounting and Finance, 2019)
This study entitled "The Effect of Consumer Price Index and the Money Supply on Net Asset Value of Islamic Mutual Funds", This study aims to analyze the effect of the Consumer Price Index and the Money Supply on the Net Asset Value of Islamic Mutual Funds. The method used in this research on Islamic Mutual Funds uses a quantitative approach. The data collection technique used is by using the saturated sampling method. The type of data used is secondary data. While the data analysis techniques used are descriptive statistics, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, multiple regression analysis, coefficient of determination test and hypothesis testing. partial does not affect the Net Asset Value of Islamic Mutual Funds in Indonesia with a comparison of tcount < ttable or -0.029 < 1.01410, while the amount of money in circulation partially affects the Net Asset Value of Islamic Mutual Funds with a comparison of tcount > ttable or 21.506 > 1.01410 . Simultaneously the Consumer Price Index and the Money Supply have a significant effect on the Net Asset Value of Islamic Mutual Funds with a comparison of fcount > ftable or 409.297 > 3.20. The conclusion is that the consumer price index has no significant effect on the net asset value of Islamic mutual funds. Meanwhile, partially, the money supply has a significant effect on the net asset value of Islamic mutual funds. And simultaneously the consumer price index and the money supply affect the net asset value of Islamic mutual funds.